The Influence of Professional Ethics and Government Accounting Standards on the Quality of Financial Reporting in Gorontalo Regency - Dahu, Marlina Ak.; Abdullah, Julie; Saprudin; Junus, Onong; Hasan, Wahyudin (Basic and Applied Accounting Research Journal, 2025)
This study aims to analyze the influence of professional ethics and government accounting standards on the quality of financial reports in Gorontalo Regency. The research employs a regression model. The results show that both professional ethics and government accounting standards collectively have a significant impact on the quality of financial reports. Partial tests also indicate that each independent variable has a positive and significant effect on the quality of financial reports. The determination test (R2) results indicate that professional ethics and government accounting standards can explain approximately 64% of the variation. In conclusion, the application of good professional ethics and appropriate government accounting standards plays an important role in enhancing accountability and transparency in public financial management.